2020
DOI: 10.1016/j.cmi.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disease severity, unimprovement, and mortality in COVID-19 patients in Wuhan, China

Abstract: Objective: In December 2019, coronavirus disease (COVID-19) emerged in Wuhan. However, the characteristics and risk factors associated with disease severity, unimprovement and mortality are unclear and our objective is to throw some light on these. Methods: All consecutive patients diagnosed with COVID-19 admitted to the Renmin Hospital of Wuhan University from January 11 to February 6, 2020, were enrolled in this retrospective cohort study. Results: A total of 663 COVID-19 patients were included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
556
5
37

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(641 citation statements)
references
References 11 publications
43
556
5
37
Order By: Relevance
“…It is interesting that although the data in this study showed no difference in the infection rates of essential organ-related comorbidities between men and women, men were prone to have a poor prognosis. The result was consistent with another report presenting male was an independent risk factor to influence the improvement of COVID-19 patients [7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is interesting that although the data in this study showed no difference in the infection rates of essential organ-related comorbidities between men and women, men were prone to have a poor prognosis. The result was consistent with another report presenting male was an independent risk factor to influence the improvement of COVID-19 patients [7].…”
Section: Discussionsupporting
confidence: 93%
“…Twenty-five patients died and the mortality rate was 11.8%(25/212). The mortality rate in our study was higher than that indicated in other reports [7,8] in China but similar to that reported in Italy [9]. This heterogeneity is probably due to differences in the case inclusion criteria.…”
Section: Discussionsupporting
confidence: 81%
“…Older age and male sex have already been described as risks factor for severe disease and death in patients with COVID-19 [5,[11][12][13][14][15][16], although large outcome studies are needed to assess the latter. The most interesting finding of our analysis is that severe obesity is a significant factor for severe respiratory disease and death in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The virus is equally transmissible in all ages; however, people who are now in critical conditions or who died were more likely to be in older age and found they had one or more morbidities [8][9][10][11]. Commonly reported morbidities among patients who died from COVID-19 were hypertension, diabetes, cardiovascular disease, and cerebrovascular disease [8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%